Validation of the PedsQL Epilepsy Module: A pediatric epilepsy‐specific health‐related quality of life measure. (13th September 2017) - Modi, Avani C.; Junger, Katherine F.; Mara, Constance A.; Kellermann, Tanja; Barrett, Lauren; Wagner, Janelle; Mucci, Grace A.; Bailey, Laurie; Almane, Dace; Guilfoyle, Shanna M.; Urso, Lauryn; Hater, Brooke; et al.
Summary: Objective: To validate a brief and reliable epilepsy‐specific, health‐related quality of life (HRQOL) measure in children with various seizure types, treatments, and demographic characteristics. Methods: This national validation study was conducted across five epilepsy centers in the United States. Youth 5–18 years and caregivers of youth 2–18 years diagnosed with epilepsy completed the PedsQL Epilepsy Module and additional questionnaires to establish reliability and validity of the epilepsy‐specific HRQOL instrument. Demographic and medical data were collected through chart reviews. Factor analysis was conducted, and internal consistency (Cronbach's alphas), test–retest reliability, and construct validity were assessed. Results: Questionnaires were analyzed from 430 children with epilepsy (Mage = 9.9 years; range 2–18 years; 46% female; 62% white: non‐Hispanic; 76% monotherapy, 54% active seizures) and their caregivers. The final PedsQL Epilepsy Module is a 29‐item measure with five subscales (i.e., Impact, Cognitive, Sleep, Executive Functioning, and Mood/Behavior) with parallel child and caregiver reports. Internal consistency coefficients ranged from 0.70–0.94. Construct validity and convergence was demonstrated in several ways, including strong relationships with seizure outcomes, antiepileptic drug (AED) side effects, and well‐established measures of executive, cognitive, and emotional/behavioral functioning. Significance: The PedsQL Epilepsy Module is a reliable measure of HRQOL with strong evidence of its validity across the epilepsy spectrum in both clinical and research settings.